2012
DOI: 10.1007/s10517-012-1613-z
|View full text |Cite
|
Sign up to set email alerts
|

Studies of oxidant-induced changes in albumin transport function with a fluorescent probe K-35. Effect of hypochlorite

Abstract: The dynamics of changes in albumin transport function during hypochlorite-induced oxidation of isolated albumin in blood plasma and serum was studied with a fluorescent probe K-35. Binding of the probe K-35 to albumin was characterized by effective concentration of albumin. Oxidative modification of proteins was evaluated by the content of carbonyl products of protein oxidation and bityrosine fluorescent products. Oxidation with hypochlorite was accompanied by a decrease in the effective concentration of album… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…It has bactericidal activity but it has become apparent that collateral damage to host tissues is a key event in a number of human pathologies linked with inflammation. Rate constants , for reaction of hypochlorite with individual biological components have shown that proteins are by far the major targets for hypochlorite in plasma, and HSA, as the most abundant protein, is thought to be the most probable target in general. Oxidatively modified forms of HSA have indeed been detected in several pathological conditions characterized by oxidative stress, and the characterization of model systems of oxidized HSA has mainly been addressed through chemical essays or mass spectrometry methods to quantify and identify chemical modifications induced by hypochlorite, , as well as by detecting spectral variations in UV absorption and fluorescence spectroscopy. …”
Section: Introductionmentioning
confidence: 99%
“…It has bactericidal activity but it has become apparent that collateral damage to host tissues is a key event in a number of human pathologies linked with inflammation. Rate constants , for reaction of hypochlorite with individual biological components have shown that proteins are by far the major targets for hypochlorite in plasma, and HSA, as the most abundant protein, is thought to be the most probable target in general. Oxidatively modified forms of HSA have indeed been detected in several pathological conditions characterized by oxidative stress, and the characterization of model systems of oxidized HSA has mainly been addressed through chemical essays or mass spectrometry methods to quantify and identify chemical modifications induced by hypochlorite, , as well as by detecting spectral variations in UV absorption and fluorescence spectroscopy. …”
Section: Introductionmentioning
confidence: 99%
“…The content of carbonyl products was measured as described previously with modifications [ 56 ]. The reaction mixtures (200 µL) were composed of 50 µmol·L −1 HSA and 500 µmol·L −1 Tau-NBr 2 or 1000 µmol·L −1 Tau-NHCl in 10 mmol·L −1 PBS at 25 °C and incubated for 1 h; then, 1000 µmol·L −1 methionine was added to scavenge the remaining oxidants.…”
Section: Methodsmentioning
confidence: 99%
“…During the exper iments, dye concentrations in solutions were varied in a range of (1-5) × 10 -6 mol/L; equal volumes of MNPs and protein containing samples were placed into a cell with a dye solution. The degrees of the probe-protein interaction in different samples were comparatively estimated in terms of effective protein concentration (c eff , %), which is equal to the fluores cence intensity ratio between probe-protein com plexes in MNPs containing and MNPs free (refer ence) samples [26].…”
Section: Methodsmentioning
confidence: 99%